Investigation of Apurinic/Apyrimidinic Endonuclease 1 Expression Changes in Prostate Cancer - Rouhi, Vahid; Habibi, Sanaz; Baykal Koca, Sevim; Köseoğlu, Hikmet; Güven, Mehmet (Cerrahpaşa Medical Journal, 2025)
Objective: Prostate cancer, a leading cause of cancer deaths in men, involves genetic alterations and DNA damage. Oxidative stress–induced DNA damage is crucial in its development, necessitating efficient DNA repair mechanisms. Base excision repair (BER), a key pathway, addresses oxidative DNA damage with enzymes like Apurinic/Apyrimidinic Endonuclease 1 (APE1). Recent findings show that altered APE1 expression disrupts BER balance, contributing to genomic instability and cancer progression. This study examines APE1 expression in prostate cancer tissues to clarify its role in cancer development and therapeutic implications. Assessing APE1 expression in prostate cancer may elucidate its role in tumor progression, therapeutic resistance, and genomic instability, offering deeper insights into the mechanistic relevance of the BER pathway in oncogenesis. Methods: A total of 50 male patients diagnosed with prostate cancer were included in this study. Tumor and adjacent normal tissue samples were collected from consecutive male patients who underwent Tru-cut prostate biopsies due to clinical suspicion of prostate cancer, and gene expression levels were analyzed using real-time polymerase chain reaction. Results: The results showed no significant difference in APE1 expression between tumor and normal tissues (P > .05). Clinical factors like smoking, age, diabetes, hypertension, PIRADS, and Gleason scores did not significantly correlate with APE1 expression. However, a statistically significant correlation was observed between PSA levels and APE1 expression (r: 0.287, P = .04). Conclusion: The authors’ findings suggest that while no substantial changes in APE1 expression were observed in prostate cancer tissues, the enzyme’s role in DNA repair remains crucial. Abnormalities in APE1 expression and function can contribute to genomic instability and cancer progression. Future studies with larger sample sizes and standardized methodologies are necessary to better understand the potential role of APE1 as a biomarker and therapeutic target in prostate cancer. Cite this article as: Rouhi V, Habibi S, Baykal Koca S, Köseoğlu H, Güven M. Investigation of apurinic/apyrimidinic endonuclease 1 expression changes in prostate cancer. Cerrahpaşa Med J 2025, 49, 0009, doi: 10.5152/cjm.2025.25009.